KREATIVITAS DIGITAL MARKETING UNTUK KEWIRAUSAHAAN MAHASISWA DI KECAMATAN CIAWI - Imas Maesaroh; Ginta Ginting; Devi Ayuni; Andriyansah Andriyansah; Lina Mufidah Amatillah (Yayasan Lavandaia Dharma Bali, 2024)
The urgency of this activity is to promote student products so that the products can be femilar in the market. The purpose of this community service activity is to provide assistance starting from management, packaging to marketing (promotion with digital marketing applying economic analysis using BMC (Bussines Model Canvas) BMC is very helpful to speed up the process of analysing the strengths and weaknesses of the business. By knowing the strengths and weaknesses, the analysis of needs and profits can be done quickly and effectively). The partner in this activity is